Supply Chain Management of Kurban Cattles in 'Tebar Hewan Kurban' Program, Dompet Dhuafa Republika - Rimi Gusliana Mais; Zainal Abidin (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to reformulate beef cattle supply chain management based on a case study in the Dompet Dhuafa Republika (DDR) program 'Tebar Hewan Kurban' (THK). This qualitative descriptive study is based on a survey in 15 locations for the empowerment of beef cattle farmers who are THK partners outside Java, and observations on program implementation along the supply chain in 2020. The beef cattle supply chain as a result of this study is described in the figure and compared with the supply chain of Kurban animals from previous studies. The results showed that the management of the cattle supply chain in THK's DDR program provided tangible benefits for partner farmers. The results of this study are expected to open new insights about the economic aspects of the implementation of Kurban that provide greater benefits to small farmers, without forgetting other stakeholders involved in the program. This paper contributes to filling the literature gap and empirical studies on community empowerment programs related to Kurban ritual activities that are still rarely carried out until now.